Higenamine Attenuates Neuropathic Pain by Inhibition of NOX2/ROS/TRP/P38 Mitogen-Activated Protein Kinase/NF-ĸB Signaling Pathway - Yang, Bing; Ma, Shengsuo; Zhang, Chunlan; Sun, Jianxin; Zhang, Di; Chang, Shiquan; Lin, Yi; Zhao, Guoping (Frontiers in Pharmacology, 2021)
Oxidative stress damage is known as one of the important factors that induce neuropathic pain (NP). Using antioxidant therapy usually achieves an obvious curative effect and alleviates NP. Previous pharmacological studies have shown that higenamine (Hig) performs to be antioxidant and anti-inflammatory. However, the protective effect and mechanism of Hig on NP are still unclear. This study mainly evaluated the changes in reactive oxygen species (ROS) level, lipid peroxidation, and antioxidant system composed of superoxide dismutase (SOD) and glutathione (GSH) through chronic constrict injury (CCI) model rats and t-BHP-induced Schwann cell (SC) oxidative stress model. The expressions of two inflammatory factors, tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), were also assessed. The possible molecular mechanism of Hig in the treatment of NP was explored in conjunction with the expression of mitochondrial apoptosis pathway and NOX2/ROS/TRP/P38 mitogen-activated protein kinase (MAPK)/NF-ĸB pathway-related indicators. Hig showed substantial antioxidant and anti-inflammatory properties both in vivo and in vitro. Hig significantly reduced the upregulated levels of ROS, malondialdehyde (MDA), TNF-α, and IL-6 and increased the levels of SOD and GSH, which rebalanced the redox system and improved the survival rate of cells. In the animal behavioral test, it was also observed that Hig relieved the CCI-induced pain, indicating that Hig had a pain relief effect. Our research results suggested that Hig improved NP-induced oxidative stress injury, inflammation, and apoptosis, and this neuroprotective effect may be related to the NOX2/ROS/TRP/P38 MAPK/NF-ĸB signaling pathway.